Significant overexpression of the Merkel cell polyomavirus (MCPyV) large T antigen in Merkel cell carcinoma. Issue 2 (6th February 2012) - Erovic, Boban M.; Al Habeeb, Ayman; Harris, Luke; Goldstein, David P.; Ghazarian, Danny; Irish, Jonathan C.
Abstract Background The purpose of this study was to determine the expression pattern of the Merkel cell polyomavirus (MCPyV) large T‐protein antigen in patients with Merkel cell carcinoma. Methods A tissue microarray (TMA) containing 30 specimens was constructed and stained for the MCPyV large T protein. Immunohistochemical expression was determined semiquantitively and was compared to patients' outcome. Results Nuclear expression of MCPyV large T protein was detected in 29 of 30 specimens (97%). In particular, 60% to 100%, 30% to 60%, and 10% to 30% of tumor cells were positive in 27 specimens (90%), 1 (3%), and 1 (3%), respectively. There was no difference in positivity between primary and metastatic lesions. Clinical data could not be correlated to MCPyV large T‐protein expression. Conclusion MCPyV large T protein was significantly overexpressed in 97% of all specimens. Although we could not demonstrate a predictive effect, MCPyV large T protein may represent a molecular marker with utility in pathological diagnosis as well as a potential new therapeutic target in patients with Merkel cell carcinoma. © 2012 Wiley Periodicals, Inc. Head Neck, 2013